Wason Selection Task and a Semantics Based on State-descriptions. - López-Astorga, Miguel (Problems / Problemos, 2022)
Peter Wason provided his four-card selection task over five decades ago. It keeps causing difficulties from both the linguistic, the psychological, and the cognitive point of view. Many psychology theories have been proposed in order to remove its problems. This paper tries to offer one more possible account. That account is based on the method of extension and intension presented by Rudolf Carnap. Hence, it resorts to the concept of state-description. The basic ideas of the argumentation are two: 1) people might tend to consider state-descriptions when processing information, and 2) if conditionals are not expressed with a clear contextual framework, they might be interpreted as biconditionals.